Jenis - Jenis Hama Penting Pada Beberapa Varietas Kedelai (Glicyne max L Merrill) Berdaya Hasil Tinggi Di Kampung Sidey Makmur, Sidey Manokwari - Nelince Insyur; Johannes Tethool; Yacob Bodang (Agrotek, 2012)
The study aimed to identify the presence and the population of insect pest to the cultivation of highest productivity soybean. The study designed in randomized block design with the treatments are 6 varieties of soybean such as Anjasmoro (V1), Burangrang (V2), Grobogan (V3), Rajabasa (V4), Detam-1 (V5) and local variety (V6). The data were statistically analyzed and further tested by Duncan (DMRT). The result showed that Ophiomyia phaseoli, Lamprosema indicata, Nezara virudula, Riptortus lineavis, and Etiella zinckenella were the main insects pest found in the 6 varieties tested. Analysis of variance showed that the majority of pest insect populations did not differ between the varieties tested, except for observations at 4 and 5 weeks after planting. The population of beetles mostly found at 11 weeks after planting. The population of insect pest at Anjasmoro variety relatively low compared to other varieties. All tested varieties can be used to increase the productivity of soybean, especially Anjasmoro variety, but the presence of Lamprosema indicata need to be aware at 4 to 5 weeks after planting especially for Detam-1 and Rajabasa varieties.